1996
DOI: 10.1016/0014-5793(95)01519-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of classical inwardly rectifying potassium channel mRNAs in the brain: comparison of IRK2 with IRK1 and IRK3

Abstract: Distribution of IRK2 inwardly rectifying potassium channel mRNA in the mouse brain was studied using in situ hybridization histochemistry and compared with those of other classical inwardly rectifying potassium channel (IRK1 and IRK3) mRNAs. All these IRK channel mRNAs were detected in neurons, but not in glial cells. Their distribution patterns in the brain were, however, quite divergent: IRK2 mRNA was detected extremely high in granule cells of cerebellum, relatively high in motor trigeminai nucleus and mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…2, D-F). The distribution of Kir2.3 immunoreactivity was consistent with that of its mRNA shown by in situ hybridization studies (5,11,16,17). Figure 2, C-F, depicts the immunolocalization of Kir2.3 in mouse OB at higher magnification.…”
Section: Characterization Of Anti-kir23 Antibodysupporting
confidence: 79%
See 3 more Smart Citations
“…2, D-F). The distribution of Kir2.3 immunoreactivity was consistent with that of its mRNA shown by in situ hybridization studies (5,11,16,17). Figure 2, C-F, depicts the immunolocalization of Kir2.3 in mouse OB at higher magnification.…”
Section: Characterization Of Anti-kir23 Antibodysupporting
confidence: 79%
“…2F). Whereas Kir2.3 mRNA was expressed predominantly in the granule cells (5,11,16), no clear immunoreactivity was detected in somata of granule cells (Fig. 2F).…”
Section: Characterization Of Anti-kir23 Antibodymentioning
confidence: 97%
See 2 more Smart Citations
“…Double-label immunofluorescence controls included dual-channel recordings of single-labeled cultures to exclude possible bleeding-through of the detected signals. Specificity of the affinity-purified Kir2.2 and Kir2.3 antibodies also was checked by examining sections of rat brain to determine whether the staining pattern matched that found using mRNA localization techniques (Falk et al, 1995;Horio et al, 1996); these experiments revealed a consistent match between antibody staining and mRNA distributions. The distribution pattern was also similar to that of a recent report using a different set of antibodies (Pruss et al, 2005).…”
Section: Methodsmentioning
confidence: 99%